I Certamen Crono-Teatro (2013). Modalidad de andén 4. El Kebab de Pinter - Pygmalión, (Pygmalion. Revista de teatro general y comparado, 2025)
I Certamen Crono-Teatro (2013). Modalidad de andén 4. El Kebab de Pinter